2023
DOI: 10.3390/ijms24065709
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence of Mitochondrial Dysfunction in Osteomyelitis Patients

Abstract: Osteomyelitis is a difficult-to-treat disease with high chronification rates. First studies suggest increases in mitochondrial fission and mitochondrial dysfunction as possible contributors to the accumulation of intracellular reactive oxygen species and thereby to the cell death of infected bone cells. The aim of the present study is to analyze the ultrastructural impact of bacterial infection on osteocytic and osteoblastic mitochondria. Human infected bone tissue samples were visualized via light microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“… 29–31 A recent study by Tsvetkov et al 2022, 32 identified a new cell death pathway, cuproptosis, characterized by intracellular copper accumulation that triggers lipid peroxidation, mitochondrial enzyme aggregation, and destabilization of iron-sulfur (Fe-S) cluster proteins, leading to cell death. Additionally, Mendelsohn et al 2023, 33 observed mitochondrial dysfunction in patients with chronic osteomyelitis, linking it to the accumulation of intracellular reactive oxygen species that induce osteoblast cell death. Interestingly, another study found that using an inhibitor that targets the Programmed cell death 1/Programmed cell death ligand 1 (PD-1/PD-L1) pathway significantly reduced mitochondrial autophagy in F4/80 macrophages in S. aureus -infected osteomyelitis, which in turn decreased bone destruction in affected mice.…”
Section: Introductionmentioning
confidence: 99%
“… 29–31 A recent study by Tsvetkov et al 2022, 32 identified a new cell death pathway, cuproptosis, characterized by intracellular copper accumulation that triggers lipid peroxidation, mitochondrial enzyme aggregation, and destabilization of iron-sulfur (Fe-S) cluster proteins, leading to cell death. Additionally, Mendelsohn et al 2023, 33 observed mitochondrial dysfunction in patients with chronic osteomyelitis, linking it to the accumulation of intracellular reactive oxygen species that induce osteoblast cell death. Interestingly, another study found that using an inhibitor that targets the Programmed cell death 1/Programmed cell death ligand 1 (PD-1/PD-L1) pathway significantly reduced mitochondrial autophagy in F4/80 macrophages in S. aureus -infected osteomyelitis, which in turn decreased bone destruction in affected mice.…”
Section: Introductionmentioning
confidence: 99%